An Association of UDP-Glucuronosyltransferase 2B7 C802T (His268Tyr) Polymorphism with Bladder Cancer in Benzidine-Exposed Workers in China - Lin, Guo-fang; Guo, Wei-chao; Chen, Ji-gang; Qin, Yi-qing; Golka, Klaus; Xiang, Cui-qing; Ma, Qing-wen; Lu, Da-ru; Shen, Jian-hua (Toxicological sciences, 2005)
UDP-Glucuronyltransferase 2B7 (UGT2B7) is involved in benzidine metabolism, as demonstrated by in vitro experiments with liver slices. To evaluate the possible association of UGT2B7 gene polymorphism with bladder cancer risk for benzidine-exposed subjects, diagnosed bladder cancer cases (n = 36) who were members of a cohort of benzidine-exposed workers in the Chinese dyestuff industry were investigated. UGT2B7 polymorphism at locus C802T (His268Tyr) was detected using a PCR-RFLP based procedure. Nondiseased cohort members (156 men, 95 women) were taken as work-related control, and unexposed healthy individuals (113 men, 105 women) were taken as community control. The data showed that the polymorphism at locus UGT2B7 C802T in a general Chinese population significantly differs from that in a Caucasian population (p = 0.00018), displaying a distinctly lower frequency of T/T genotypes (9.2 vs. 25.3%), while no significant difference to a Japanese population could be detected (p = 0.17). A higher prevalence of T/T genotype carriers was found in the cancer cases, compared with unexposed healthy controls (25 vs. 9%, odds ratio [OR] 3.30, 95% confidence interval [95% CI] 1.37–7.98, p = 0.006). A higher presentation of T allele carriers in the patients group was also confirmed (46 vs. 33%, OR 1.73, 95% CI 1.05–2.87, p = 0.03). A higher portion of the T/T genotype was also observed in bladder cancer patients compared with nondiseased members of the same benzidine-exposed cohort, although some of them displayed different degrees of cellular alterations in their exfoliated urothelial cells. This study points for the first time to an association between a homozygous mutant genotype of human UDP-glucuronosyltransferase 2B7 catalyzing the biotransformation of benzidine and an elevated bladder cancer risk for formerly benzidine-exposed workers of the dyestuff industry.